2022
DOI: 10.1021/acsnano.2c08753
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Based Nanomaterial-Induced Root Nodulation Is Modulated by Flavonoids to Improve Soybean (Glycine max) Growth and Quality

Abstract: Innovative technology to increase efficient nitrogen (N) use while avoiding environmental damages is needed because of the increasing food demand of the rapidly growing global population. Soybean (Glycine max) has evolved a complex symbiosis with N-fixing bacteria that forms nodules to fix N. Herein, foliar application of 10 mg L −1 Fe 7 (PO 4 ) 6 and Fe 3 O 4 nanomaterials (NMs) (Fe-based NMs) promoted soybean growth and root nodulation, thus improving the yield and quality over that of the unexposed control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 93 publications
(156 reference statements)
1
9
0
Order By: Relevance
“…The increased soil OM (from 46 to 53 g kg –1 ) under the addition of nano-Fe 3 O 4 could be associated with the adsorption of fulvic acid (one of the humic substances) on the surfaces of Fe 3 O 4 NPs through chemical reactions . Nanomaterials are known to have a wide range of potential applications in agriculture, including providing efficient nutrient delivery, crop protection strategies, and responsive phytohormones. , In comparison to chelated Fe, the nano-Fe was the most efficient source of Fe and it can enhance Fe solubility and its subsequent uptake by the plant (either by roots or leaves) due to its smaller particle size and larger surface area . For example, foliar application of nano-Fe can lead to greater growth than conventional Fe chelates .…”
Section: Resultsmentioning
confidence: 99%
“…The increased soil OM (from 46 to 53 g kg –1 ) under the addition of nano-Fe 3 O 4 could be associated with the adsorption of fulvic acid (one of the humic substances) on the surfaces of Fe 3 O 4 NPs through chemical reactions . Nanomaterials are known to have a wide range of potential applications in agriculture, including providing efficient nutrient delivery, crop protection strategies, and responsive phytohormones. , In comparison to chelated Fe, the nano-Fe was the most efficient source of Fe and it can enhance Fe solubility and its subsequent uptake by the plant (either by roots or leaves) due to its smaller particle size and larger surface area . For example, foliar application of nano-Fe can lead to greater growth than conventional Fe chelates .…”
Section: Resultsmentioning
confidence: 99%
“…Investigations of the plant-soil system have generally highlighted the superior efficacy of nanoscale Fe fertilizers compared to their conventional counterparts. 30,31,40,41 A previous study showed that Fe-bearing particles were detected in roots but not in shoots. 31 The accumulation of Fe in tomato tissues could be attributed to (1) Fe 7 (PO 4 ) 6 NMs acting as an efficient Fe source, thereby Environmental Science: Nano Paper increasing soil Fe bioavailability.…”
Section: Resultsmentioning
confidence: 98%
“…We previously evaluated the effects of the released P from Fe-P NMs on plant growth. 30 Two concentrations were utilized: P-low (equilibrium concentration of P from 10 mg L −1 Fe 7 (PO 4 ) 6 NMs in DI water, 93 μg L −1 P 2 O 5 ) and P-high (traditional P fertilizer dosage, 1200 mg L −1 P 2 O 5 ). The results indicated that there was no significant difference in the growth parameters, such as dry and fresh weight, plant height, chlorophyll content, and the number of nodules between the control and P-low, and P-high had no significant effects on physical parameters, except for a notable 8.5% increase in plant height compared to the control group.…”
Section: Plant Growth and Nm Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the unique physicochemical characteristics, quantum effects, and large surface area, nanomaterials (NMs) have been used in many fields such as food chemistry, catalysis, , medical, , environmental, , pollution remediation, and energy. , In recent years, nanoagriculture has emerged as a potential application area for NMs. , NMs have been investigated for their possible application in agriculture as nanofertilizers, , nanopesticides, , growth regulators, biosensors, and targeted transporters. ,, With considerable advancements in the synthesis and characterization of NMs as well as a greater mechanistic knowledge of nanomaterial–plant interactions, the application of nanotechnology in agriculture has grown significantly over the past 10 years. The development of highly specialized, even responsive, nanomaterials and their fine-tuning have enormous potential as a long-term approach to agricultural enhancement.…”
Section: Introductionmentioning
confidence: 99%